2022
DOI: 10.1155/2022/7273387
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Inhibits Inflammation in Rats with Chronic Obstructive Pulmonary Disease by the TLR2/MYD88/NF-κBp65 Signaling Pathway

Abstract: Objective. Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory disease with a relatively high morbidity and death rate. This study aimed to investigate the inhibitory effect of baicalin (BA) on inflammation in COPD rats and its possible mechanism. Methods. The experimental COPD of SD rats were induced by LPS, smoking, and cold stimulation, and they were randomly divided into the control group, COPD group, COPD + LB group, COPD + MB group, and COPD + HB group. The test of pulmonary function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Mechanistically, acacetin could bind MEK1/2, ERK1/2, Bcl2, NF-κB, and alCDase according to the results of our docking analysis, which elucidates the signaling modulation by QJHTD and indirectly testifies to the role of acacetin as an effective compound in this preparation. However, molecular docking exhibited low affinity between baicalin and target proteins, indicating that baicalin may exert its action on COPD via distinct signaling cascades, as previously reported [ [42] , [43] , [44] ]. Overall, acacetin and baicalin may act synergistically via complementary molecular routes to assist in the anti -COPD properties of QJHTD.…”
Section: Discussionsupporting
confidence: 61%
“…Mechanistically, acacetin could bind MEK1/2, ERK1/2, Bcl2, NF-κB, and alCDase according to the results of our docking analysis, which elucidates the signaling modulation by QJHTD and indirectly testifies to the role of acacetin as an effective compound in this preparation. However, molecular docking exhibited low affinity between baicalin and target proteins, indicating that baicalin may exert its action on COPD via distinct signaling cascades, as previously reported [ [42] , [43] , [44] ]. Overall, acacetin and baicalin may act synergistically via complementary molecular routes to assist in the anti -COPD properties of QJHTD.…”
Section: Discussionsupporting
confidence: 61%
“… Hao et al (2021) demonstrated that baicalin upregulated the expression of heat shock protein 72 (HSP72), resulting in the inhibition of c-Jun N-terminal kinase (JNK) signaling activation and ultimately relieving COPD. Recently, Ju et al (2022) proved that baicalin controlled the TLR2/myeloid differentiation primary response gene 88 (MYD88)/NF-κB p65 signaling pathway to reduce oxidative stress and the inflammatory response in COPD rats. Through regulating oropharyngeal microbiota and influencing the expression of the High Mobility Group Protein 1 (HMGB1)/Caspase1 pathway, baicalin may also mitigate mouse lung inflammatory injury caused by exposure to PM2.5 ( Deng et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…A study from 2021 showed that a high number and blockwise distribution of certain methyl esters of pectins were responsible for a TLR2/1-dependent anti-inflammatory effect [87]. Interestingly, the flavonoid baicalin isolated from Scutellaria baicalensis Georgi inhibited inflammation in rats with chronic obstructive pulmonary disease via the TLR2/MyD88/NF-κB pathway [88]. Furthermore, the anti-inflammatory properties of TLR2 were evident in response to polysaccharide A (PSA) from Bacteroides fragilis in B cells and T cells, resulting in the production of IL-10 and interferon-γ (IFN-γ) [89][90][91].…”
Section: Tlr2 Mediates Both Pro-and Anti-inflammatory Responsesmentioning
confidence: 99%